THE IMAGE UNIVERSE FEMININE IN 60 DECADE: A LOOK IN THE PUBLISH IMAGES IN CLAUDIA'S MAGAZINE. (Fiep Bulletin - online, 2014)
The objectives in this work were: to explicit the differents feminine senses associate to the leisure moments, that shows in the images propagated by Claudia's magazine in the period between 1960 - 1969 and to identify the myths presents in the image speech in the magazine. For this, we analyzed the narratives and images pictografics in the periodic in question, in the determined period, put in central our vision in the ideologic character, in a tried in to elucidate the underlined senses in your production. Ewe analyze the speech in the text and image composition in the magazine and we saw in the 60 decade show a fragile woman, comprehensible, helpful, elegant, with a natural instinct to the sacrifice and to dedication to the others. This myth configuration about the feminine that pass between the images point this alternation between Demeter and Hera. Demeter was emblematic woman - mother image and Hera in the cares with the marriage, in the sense in being a guard or this institution. However, broke this culture barrier constructed by a society that values prior the wife and mother persons, Aphrodite shows up shied in the 60 decade in the woman sexuality awake. When get in contact with this energy, that is in leisure moments, the woman started a reconciliation process with her femininity, allows the brake of her sensuality stuck by the social interdictions. Interdictions that establish the persons. In the time, blocking the creative explosion of feminine Eros.
Keywords: Imaginative; woman; leisure